THE MEDIATION ROLE OF ORGANIZATIONAL SLACK AND INNOVATION CLIMATE ON THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT IN ACADEMIC PERFORMANCE - MEERO, DILSHAD TAHA (Journal of Duhok University, 2020)
The main objective of this research is to examine the mediation role of both organizational slack and innovation climate on the effect of perceived organizational support on academic performance at the colleges of Duhok University by using path analysis. The research reviews the contributions of researchers on the subjects of perceived organizational support (POS), organizational slack (OS), innovation climate (IC), and academic performance (AP). Constructing on previous studies, a set of hypotheses are formulated to express the effect of the POS, OS, IC variables on AP variable. A sample of 181 lecturers were selected to verify research hypotheses which have been proposed. Finally, the main conclusions of the research are presented. The results of the investigation reveal that the organizational slack and innovation climate variables mediates the influence between the perceived organizational support and the academic performance and that the indirect effect between the perceived organizational support and the academic performance was stronger than the direct influence between them.